Bio Active Solvent Free Synthesis of 7,7-dimethyl-4-Phenyl -Tetra Hydro Quinazaloine-(1H,3H)- 2,5-Diones Derivatives Employing Methanesulfonic Acid - Chinnayya Setty; N. Krishnarao; B. V. Durgarao; V. Narasingrao; P. Ramalakshmi; Shaik Lakshman (Challenges and Advances in Chemical Science Vol. 7, 2021)
Considerable attention has been focused on the synthesis of 7,-dimethyl-4-phenyl tetrahydroquinazalones- (1H, 3H)-2, 5-diones derivatives due to having a broad spectrum of biological activities such, antibacterial activity and fungicidal. As a part of our research work in this area the present investigation of efficient and cost-effective method for the synthesis of 7,7-dimethyl-4-phenyl tetrahydroquinazalones-(1H,3H)-2,5-diones derivatives employing dimedone, urea and substituted aromatic aldehyde using Methanesulfonic acid as catalyst under solvent free condition. Characterization and structural elucidation of the products was realized based on chemical, analytical and spectral analyses .The newly synthesized compounds were analyzed by 1H-NMR &13CNMR, Mass spectral and Elemental analysis. Antimicrobial activities of the titled compounds were also examined by various strains and exhibited mild to moderate anti-bacterial and anti-fungal activities.